Implementasi Platform Wayground Berbasis Gamifikasi untuk Meningkatkan Pemahaman Mahasiswa dalam Mata Kuliah Evaluasi Pembelajaran Pai Unu Purwokerto - Rosyida Nur Azizah; Nur Ali Subhan (YASIN, 2026)
Although the use of online media in Islamic Religious Education (PAI) learning has received attention in various studies, research that specifically examines the use of an intensively gamified mobile learning platform in the Learning Evaluation course remains limited. This study aims to analyze and demonstrate the extent to which the implementation of the gamification-based Wayground platform can improve students’ understanding in the PAI Learning Evaluation course at UNU Purwokerto. This study employed a mixed methods approach with a sequential explanatory design, involving 30 third-semester students selected through a purposive sampling technique. Data were collected through multiple-choice and essay tests, non-participant observation, semi-structured interviews, and documentation, and were then analyzed using a paired sample t-test and an interactive analysis model. The results showed a significant increase in the mean score from 74.34 to 86.09, representing an increase of 11.75 points, with a significance value of < 0.001. These findings indicate that the Wayground platform is effective in improving students’ cognitive understanding and interactivity, although its level of effectiveness falls within the moderate category (N-Gain = 0.457), and therefore still requires pedagogical support from lecturers for learning outcomes to be more optimal. This study contributes to the development of digital learning models in the environment of Private Islamic Higher Education Institutions and reinforces motivation theory in technology-based learning.